Association between dietary patterns and hypertension among Han and multi-ethnic population in southwest China - Yuan Ruan; Yongshou Huang; Qiang Zhang; Shu Qin; Xiaoxia Du; Yongxin Sun (BMC, 2018)
Abstract Background Different dietary patterns and the risks of hypertension in various diet exposures among multi-ethnic population in southwest China remain extremely scarce. The aim of this study is to identify dietary patterns and explore the association between dietary patterns and the risk of hypertension among Han and multi-ethnic population in southwest China. Methods A representative sample of 3591 participants of Han, and multi-ethnic population were recruited by stratified cluster sampling in Diqing of Yunnan Province, southwest China from September 2012 to January 2013. Participants who were under 18 years old or who could not clearly answer the questions and those who used the anti-hypertensive medication were excluded from this survey. All participants reported their dietary intakes using validated food frequency questionnaires (FFQ), and their blood pressures were measured by standardized procedures. Hypertension was defined as systolic blood pressure (SBP) ≥ 140 mmHg and/or diastolic blood pressure (DBP) ≥ 90 mmHg. Dietary patterns were identified by factor analysis with principal component. Logistic regression was used to explore the association between dietary patterns and hypertension. Results The overall prevalence of hypertension was 30.5% among Han and multi-ethnic population in Diqing, Yunnan Province. Three dietary patterns were identified in this study, defined as 'Grassland healthy', 'Tuber and meat', and 'Fruit and vegetable'. Participants in the 5th quintile of the three dietary patterns were at a lower risk of hypertension compared with those in the 1st quintile. The odds ratio (OR) for the 5th quintile of 'Grassland healthy' pattern, 'Tuber and meat' and 'Fruit and vegetable' was 0.693 (95% CI: 0.537-0.893, p = 0.005), 0.678 (95% CI: 0.530-0.868, p = 0.002), 0.759 (95% CI: 0.593-0.970, p = 0.028), respectively. After further adjustment of participants' age, the negative association between the 'Grassland healthy' pattern and the prevalence of hypertension persisted (OR = 0.703, 95% CI: 0.535-0.924, p = 0.012). However, the significant associations between the other two dietary patterns and hypertension disappeared. Conclusions The 'Grassland healthy' dietary pattern is associated with lower risk of hypertension, whereas there is no significant associations between the other two dietary patterns and hypertension among Han and multi-ethnic population in Diqing of Yunnan province, southwest China.